Mode Couplers and Converters Based on Dual-Core Hollow-Core Photonic Bandgap Fiber - Simeng Han; Zhi Wang; Yange Liu; Hongye Li; Hu Liang; Zhenhong Wang (IEEE Photonics Journal)
We propose mode couplers and converters based on dual-core hollow-core photonic bandgap fiber (HC-PBGF) structures, which might be potential solutions for integrated all-fiber multiplexers or demultiplexers of a mode-division multiplexed (MDM) transmission system using HC-PBGFs. Coupling properties of ${\text{LP}}_{01}$ and ${\text{LP}}_{11}$ mode in the mode coupler are investigated and applied to mode separators and polarization separators. Mode transition from ${\text{LP}}_{01}$ to ${\text{LP}}_{11}$ and ${\text{LP}}_{21}$ mode are demonstrated in the mode converter whose smaller core is expected as input end and matched with single-mode fiber. The coupling between fundamental mode and high-order modes is accomplished through the resonant effect, which is fulfilled by modifying the structure parameter of the smaller core. Such mode converters based on dual-core HC-PBGF could be a promising substitute for the free-space coupling device, which is costly and not suitable for integration design in MDM systems and other hollow-core fiber experiments and applications.